1986
DOI: 10.1002/eji.1830161103
|View full text |Cite
|
Sign up to set email alerts
|

Purification of an antibody‐like protein from the sea star Asterias rubens (L.)

Abstract: Cells from sea star (Asterias rubens) axial organs stimulated with trinitrophenyl (TNP) or fluoresceinyl-haptened polyacrylamide beads and subsequently stimulated in vitro with the same antigen produced and released a specific antibody-like protein which induced lysis of haptened sheep erythrocytes in the presence of serum complement. The anti-TNP antibody-like protein isolated by ammonium sulfate precipitation, gel filtration and affinity chromatography exhibited a single precipiting peak after crossed immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

1986
1986
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 23 publications
0
18
0
1
Order By: Relevance
“…Second experiments used hapten-carrier conjugates and revealed the role of B-like, T-like cells, phagocytic cells and mammal complement (mouse C3 and C5 components have just been found) in the specific sea star immune response, within the axial organ [7]. At last, antibody-like factor was isolated and purified [12]: in 2000, it was shown that it presented homologies with human Kappa-like [8]. In 2007 G. Coteur mention similar results, always, with Asterias rubens [11].…”
Section: Resultsmentioning
confidence: 99%
“…Second experiments used hapten-carrier conjugates and revealed the role of B-like, T-like cells, phagocytic cells and mammal complement (mouse C3 and C5 components have just been found) in the specific sea star immune response, within the axial organ [7]. At last, antibody-like factor was isolated and purified [12]: in 2000, it was shown that it presented homologies with human Kappa-like [8]. In 2007 G. Coteur mention similar results, always, with Asterias rubens [11].…”
Section: Resultsmentioning
confidence: 99%
“…Although all efforts to find a primitive form of immunoglobulin in sea-urchin genome (Rast et al, 2006) have been unsuccessful, it is the first time, we present arguments indicating that vertebrate immunoglobulin Kappa genes are present in an invertebrate and Deuterostomes. It appears that the antibody factor has a Science Publications AJI molecular weight of 120-130.000 daltons (Delmotte et al, 1986) with 4 sub-units of 30.000 daltons each: it could be composed of 4 « kappa chains ».…”
Section: Discussionmentioning
confidence: 99%
“…1). In cooperation with the sea-star complement, they initiate the "antibody factor" (Delmotte et al, 1986) recently kappa genes were discovered in the sea-star A. Rubens (Leclerc et al, 2011). We now present the DNA structure of these genes in immunized and control sea-stars.…”
Section: Adaptative Immunity: «The Antibody Factor»mentioning
confidence: 96%
See 1 more Smart Citation
“…Sequences were assembled using Velvet (Zerbino and Birney, 2008). Delmotte et al (1986), antibody factor was isolated and purified. Leclerc (2000), it was shown that it presented homologies with human kappa-like.…”
Section: Methodsmentioning
confidence: 99%